Demokratie (aus)halten? Zwischen Anpassung und Widerstand: Spannungsfelder bei der Bildung des Demokratischen - Breser, Britta (Österreichisches Religionspädagogisches Forum, 2025)
Because democracy is under pressure in multiple respects—such as societal fragmentation, political polarization, and institutional loss of trust—the demand on democratic societies to act goes far beyond mere knowledge transmission. Such a practice of fostering the democratic necessarily operates within tensions arising from numerous, sometimes controversial, conflicts. This contribution provides an overview of selected key areas of tension that become visible and tangible in the context of cultivating the democratic across different societal domains. The focus is on the ambivalences of democracy-related educational processes—in both institutionalized and informal settings. Central to the article are insights from political science and research on civic education regarding tasks and challenges for the further development of the “democratic.” Democracy is understood not as a static goal but as an open, conflict-laden, and continuously learning way of life that must be repeatedly tested and negotiated in diverse contexts.